Pengaruh Pemahaman Mahasiswa Tentang Perbankan Syari’ah Terhadap Minat Menjadi Nasabah Di Bank Syari’ah Indonesia - Andri, Andri Marta Sudirja; Deden, Deden Ahmad Faoz Almadani; Ilham, Ilham Sidiq Pratama (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2023)
The purpose of this study was to determine the effect of Islamic banking students' understanding on interest in becoming customers at Indonesian Islamic banks, because based on the results of initial observations that have been made there are still many banking students who lack understanding to use Islamic banking services so that they still use conventional banking services. . This study aims to determine students' understanding of Islamic banking and determine their interest in becoming customers at the Islamic bank. The method used is a quantitative approach, while the research uses a descriptive method. The data collection techniques are in the form of observation and data analysis techniques using validity tests, reliability tests, classical assumption tests, simple linear regression tests and hypothesis testing using product moment correlation with the help of the IBM SPSS Statistics application so as to obtain the results, namely: 1) Understanding of Islamic banking study program students 'ah Universitas Islam Nusantara regarding Islamic banking was stated quite well with the most agree answers to the questionnaire. 2) The interest of students of Islamic banking study program at Nusantara Islam University to become customers at Indonesian Islamic banks is stated to be quite good with the most agreeable answers to the questionnaire. 3) Based on the calculation results of the hypothesis test on partial significance, it can be explained that there is a significant and positive influence between the independent variable (student understanding) on the dependent variable (interest in being a customer).   Keywords: Student Understanding of Islamic banking, Interest in Becoming a Customer   ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui pengaruh pemahaman mahasiswa perbankan syariah terhadap minat menjadi nasabah di bank syariah indonesia, karena berdasarkan hasil observasi awal yang telah dilakukan masih banyak mahasiswa perbankan yang kurang pemahamannya untuk menggunakan jasa perbankan syari’ah sehingga mereka masih menggunakan jasa perbankan konvensional. Penelitian ini bertujuan untuk mengetahui pemahaman mahasiswa tentang perbankan syariah dan mengetahui minatnya untuk menjadi nasabah di bank syariah tersebut. Metode yang digunakan menggunakan metode pendekatan kuantitatif sedangkan penelitiannya menggunakan metode deskriptif. Adapun teknik pengumpulan data berupa observasi dan teknik analisis data menggunakan uji validitas, uji reliabilitas, uji asumsi klasik, uji regresi linear sederhana dan uji hipotesis menggunakan correlation product moment dengan bantuan aplikasi IBM SPSS Statistics sehingga memperoleh hasil yaitu: 1) Pemahaman mahasiswa prodi perbankan syari’ah Universitas Islam Nusantara tentang perbankan syari’ah dinyatakan cukup baik dengan jawaban kuesioner paling banyak setuju. 2)Minat mahasiswa prodi perbankan syari’ah Universitas Islam Nusantara menjadi nasabah di bank syari’ah Indonesia dinyatakan cukup baik dengan jawaban kuesioner paling banyak setuju. 3)Berdasarkan Hasil perhitungan uji hipotesis pada signifikan parsial dapat dijelaskan bahwa ada pengaruh secara signifikan dan positif antara variabel independen (pemahaman mahasiswa) terhadap variabel dependen (minat menjadi nasabah).